Computational study of metal free alcohol dehydrogenation employing frustrated lewis pairs - Mane, Manoj V.; Rizvi, Masood A.; Vanka, Kumar (Journal of Organic Chemistry, 2015)
The catalysis of acceptorless alcohol dehydrogenation (AAD) is an important area of research. Transition metal-based systems are known to be effective catalysts for this reaction, but developing metal free catalytic systems would lead to highly desirable cheaper and greener alternatives. With this in mind, this computational study investigates design strategies than can lead to metal free frustrated Lewis pairs (FLPs) that can be employed for AAD catalysis. A careful study of 36 different proposed FLP candidates reveals that several new FLPs can be designed from existing, experimentally synthesized FLPs that can rival or be even better than state-of-the-art transition metal-based systems in catalyzing the alcohol dehydrogenation process.

Crystal structure, computational studies, and stereoselectivity in the synthesis of 2-aryl-thiazolidine-4-carboxylic acids via insitu imine intermediate - Jagtap, Rohidas M.; Rizvi, Masood A.; Dangat, Yuvraj B.; Pardeshi, Satish K. (Journal of Sulfur Chemistry, 2016)
This article presents the synthesis of (2R/2S,4R)-2-aryl-thiazolidine-4-carboxylic acids via nucleophilic addition of L-Cysteine on aromatic aldehydes involving a yield and time-effective room temperature reaction in an aqueous DMSO medium in the presence of NaHCO3 as a base. The synthesized diastereomers were spectroscopically characterized and quantified for diastereomeric excess by liquid chromatography-mass spectrometry analysis. The impact of the type and position of substituent in aromatic aldehydes on reaction time, % yield, H-1 NMR shift at newly formed chiral center [C(2)-H], and diastereomeric excess (de%) have been investigated. A plausible mechanism for stereoselectivity via an in situ imine intermediate is proposed using real-time IR monitoring of the synthetic reaction based on the significant signals at 1597, 1593cm(-1) for imine (C=N) stretching. The imine mechanism for stereoselectivity was further supported by NMR studies of azomethine C-13 NMR signals at 159, 160ppm and by the single crystal structure of hitherto unknown (2S,4R)-3-(tert-butoxycarbonyl)-2-(2-hydroxyphenyl)thiazolidine-4-carbox ylic acid (3a) obtained as a major diastereomer in the synthesis of the butyloxy carbonyl (BOC) derivative of (2R/2S,4R)-2-(2-hydroxyphenyl)thiazolidine-4-carboxylic acid. The significant ortho-OH effect of phenolic hydroxyl group leading to strong hydrogen bondings plays a vital role in the formation of 2S,4R BOC derivative stereoselectively. The frontier molecular orbitals, possible electronic excitations, IR band characterizations, and reactivity parameters of newly reported compound (3a) have been predicted using quantum chemical descriptors from density functional theory. The theoretical exploration of experimental spectra using time-dependent DFT indicated a (-*) transition between HOMO and LUMO in the ultraviolet region.
Keywords: 2-aryl-thiazolidine-4-carboxylic acids; density function theory; frontier molecular orbitals; imine intermediate; X-ray crystal structure

Cyanuric-chloride-mediated synthesis of 2-Aryl-3-tert-butoxycarbonyl-thiazolidine-4-carboxylic acid anilides: mechanistic, X-ray crystal structures and cytotoxicity studies - Jagtap, Rohidas M.; Shaikh, Samir R.; Gonnade, Rajesh G.; Raheem, Shabnam; Rizvi, Masood A.; Pardeshi, Satish K. (ChemistrySelect, 2019)
The `2R,4R'-2-aryl thiazolidine-4-carboxylic acid anilides (ATCAAs) were synthesized using cyanuric chloride (CC) as a clean and substoichiometric acid-amine coupling agent under optimized reaction conditions. The diesterphenol intermediate based mechanism is proposed and supported by spectral characterization of the intermediate. The single crystal X-ray structures of acid substrate (2R,4R)-3-(tert-butoxycarbonyl)-2-(2-methoxyphenyl)thiazolidine-4-carbox ylic acid (3 a) and anilides (R)-tert-butyl 4-(2-fluorophenylcarbamoyl)thiazolidine-3-carboxylate (4 b), (2R,4R)-tert-butyl 2-(2,6-dichlorophenyl)-4-(m-tolylcarbamoyl)thiazolidine-3-carboxylate (6 b) confirmed the formation of chiral anilides. The synthesized library of anilides [(R)-tert-butyl 4-Aryl thiazolidine-3-carboxylate and (2R,4R)-tert-butyl 2-Aryl-4-Aryl thiazolidine-3-carboxylate] 4 a-6 f was screened for their in vitro anti cancer, neuronal and neuroprotective studies. The anilides 4 b, 4 g, 5 d, 5 h, 6 c and 6 f (where the aryl=2-fluorophenylcarbamoyl, 4-chlorophenylcarbamoyl, 2-methoxyphenyl, 2,5-dichlorophenylcarbamoyl, 2,6-dichlorophenyl, 4-chlorophenylcarbamoyl respectively)were found to be less cytotoxic towards N2 A, SHSY-5Y neuronal cell lines in their differentiated and undifferentiated forms, and also exhibited dose dependant anti-inflammatory properties for a possible identification towards neurodegenerative and inflammatory disorders.
Keywords: Acid-amine coupling; Cyanuric chloride; Cytotoxicity; Mechanistic investigations; Single crystal x-ray structure